“It’s Okay to be Slow:” Witnessing the Articulation of Connected Practices by Creative Collectives in Indonesia and Malaysia - Zaki Habibi (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2022)
This article focuses on the everyday responses of the local creatives in dealing with the problematic single narrative of creative cities. Aiming to understand the everyday creative and media practices of individuals in the creative collectives that are situated in emerging creative cities in Southeast Asia, the research specifically addresses key contemporary debates within the field of urban media and communication studies. The article gives priority to the voices of the city dwellers from a bottom-up approach, looking at the material and embodied practices in their everyday life. Empirically, this article seeks the alternative voices raised by the members of selected creative collectives - four collectives in Bandung, Indonesia, and four others in George Town, Malaysia - in articulating the meaning of creativity, the media practices involved within, and the organic ways of organizing urban collectives. Drawing insights from the notion of articulation and media practice, and by employing both ethnographic and visual methodology approaches, in particular the use of the photo-documentation method, there are three key thematic findings elaborated here. These themes are (1) social settings in media-related practices, (2) material objects and sensitive affection, and (3) the labor of love. The ways in which these are discussed, using a combination of ethnographic vignettes and photo collages, foreground the importance of cultural identity articulation practiced by the creative collectives in both cities. Thus, the interlinkage between mediated experiences, spatial practices, and visual contexts is also a key significant aspect in the analysis of these bottom-up, organic urban creativities.